Prispevek k poznavanju favne kačjih pastirjev (Insecta, Odonata) Vipavske doline (zahodna Slovenija) - Bedjanič, Matjaž (Natura Sloveniae, 2000)
An annotated list of 32 dragonfly species collected at 27 localities during the 1994-2000 period is given. Three species, viz. Ceriagrion tenellum (de Villers), Anax parthenope (Selys) and Libellula fulva Mueller, are new for theinvestigated area. The records of Coenagrion ornatum (Selys), Cerdon lindenil (Selys), Cordulegaster heros Theischinger, Somatochlora flavomaculata(Vender Linden) and Orthetrum c, coerulescens (Fabricius) are also briefly commented as they deserve attention from zoogeographical or nature conservation point of view. A list of 44 dragonfly species; hereto reported from the Vipava valley with its surroundings, is compiled and an odonatological bibliography of the investigated area is presented.
Keywords: Ecosystem; Insects; insekti; kačji pastirji; Odonata; Vipava Valley; Vipavska dolina